2018
DOI: 10.1108/ijem-09-2017-0255
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity of school teachers in the context of socio-historical dynamics of Russian society

Abstract: Purpose The purpose of this paper is to describe the specific nature of school teacher’s professional identity in the context of its stability maintenance in the Soviet and modern periods of Russian society development. Design/methodology/approach A total of 618 teachers of state comprehensive secondary schools were interviewed with a standardized questionnaire. The survey was divided into four semantic blocks: analyzing how teachers percept their own socio-economic situation; studying the structure of teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…According to Kobakhidze (2013), certification policy in some ways improved teacher performance, social status and prestige in society. Klimenko et al (2018) revealed that school teacher job had high prestige within society, was a social work and gave financial security. Ideological support from the government was highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kobakhidze (2013), certification policy in some ways improved teacher performance, social status and prestige in society. Klimenko et al (2018) revealed that school teacher job had high prestige within society, was a social work and gave financial security. Ideological support from the government was highly needed.…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting, the children like these lessons" (female, primary school teacher, 25 years old, teaching experience 4 years); "In general, anyone who knows how to use the Internet understands that you can find a large number of presentations on the necessary topics and just rewrite them for yourself" (male, Humanities, 26 years old, teaching experience 4 years). And minimize the risks that all teachers face, regardless of teaching experience, associated with an increased level of accountability and excessive bureaucracy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Highly qualified specialists -those who are the generator of new ideas in industry, in the field of high technology; the complexity of building relationships in a multicultural environment between the country's population and immigrants who differ in a specific system of values, national traditions, and various religious views. In addition, we should not forget the issue of precarization that proceeds from the job instability and might lead to the serious distortions on the labour market (see Klimenko, Posukhova, 2018).…”
Section: Threats For the Human Resources In Russiamentioning
confidence: 99%